Legal Analysis of Criminal Acts of Corruption of Livestock Budget (Study of Decision No.3038 K/Pid.Sus/2021) - Damanik, Stevi Idhel Wheis; prasetyo, Muhammad Arif; Adawiyah, Rodiatun; Ramadhana, Widodo; Sembiring, Josua Pramana Adika (LEGAL BRIEF, 2024)
One of the crimes that is always in the spotlight in Indonesia is the problem of corruption. Corruption is no longer a foreign thing in this country. Indonesian corruption is even classified as an extraordinary crime because it has damaged not only state finances and the country's economic potential, but has also destroyed the pillars of socio-cultural, moral, political and legal security of Indonesia. As happened in the decision Number 3038 K / Pid.Sus / 2021, which stated that there had been a criminal act of corruption in the grant activity budget of the East Java Provincial Animal Husbandry Service in 2016, which was carried out by the Defendant IMAM HANAFI, SE bin MUCHAMAD HABIB. The empirical normative method is the method applied in this research where this method is carried out through research activities on reading materials and directly reviewing the objects being studied. The application of Article 2 Paragraph 1 of the Corruption Eradication Law in Decision Number 3038 K/Pid.Sus/2021 to the Defendant IMAM HANAFI, Se is in accordance with the fact that the defendant is a person assigned by the East Java Provincial Animal Husbandry Service to coordinate 5 Groups that will receive grant funds to buy livestock. That the judge in deciding the case considered that the defendant's actions had fulfilled the elements of a crime in Article 2 paragraph (1) in conjunction with Article 18 of Law Number 31 of 1999 concerning the Eradication of Corruption.